Financial Management Analysis of Indonesian Migrant Workers: Case Study of Indonesian Female Migrant Workers in Singapore - Robiyatin, Siti; Muktiyanto, Ali; Fatimah, Fatia; Daulay, Pardamean (International Journal of Science and Society, 2024)
This study analyzes the financial management of female Indonesian migrant workers in Singapore. This type of research uses a quantitative descriptive approach where data is obtained by conducting interviews, questionnaires, and observations with purposive sampling of as many as 40 respondents who work in Singapore. The financial management of female PMIs is different because every female PMI is not the same in managing finances from the income or monthly salary she receives. How to manage female PMIs' finances is to record all basic needs and try to make needs not exceed income or have been as previously targeted. The rest of these basic needs are saved in the bank by opening several savings books, and if the savings are saved in the bank with the first objective of investing, then if the savings money is sufficient, female PMIs will allocate the money to invest. Property investment, including land investment, is considered one of the leading investments by Singaporean female PMIs because land prices continue to rise and are accompanied by price increases, high resale value, more affordable investment price, multifunction, easy maintenance, and direct ownership. By becoming female PMIs, their economic life has changed, and the income earned is much more than before with proper financial management.